The Urgency of Implementing Intellectual Property Regulations in the Protection of Traditional Knowledge in Indonesia - Dhimas Widyananda (Borong Newinera Publisher, 2023)
For the people of Indonesia, traditional knowledge is the most important knowledge that aims to preserve assets or wealth that is rarely owned by countries other than Indonesia. Traditional knowledge acquires the interaction between nature and the environment that belongs to every society. This study has secondary data consisting of three materials, including 1) secondary legal material, and 2) primary legal material. The material of the secondary law is in the form of articles or news about the protection of traditional knowledge, both from international and national. Then, the material of the premier law is based on Government Regulation Number 56 of 2022 concerning Communal Intellectual Property. Then, qualitatively the data was analyzed by comparing the regulations that became references with the protection of traditional knowledge. A country has cultural heritage that must be protected in order to avoid extinction, where in providing protection the state plays an active role, especially in the Indonesian state. Indonesia as a state of law applies the urgency of regulations related to the protection of traditional knowledge.